Dinámica celular en respuesta a la desmielinización inducida por intoxicación con cuprizona en diferentes condiciones experimentales - Millet, Violeta (2016)
Demyelination models have proven useful tools in the assessment of new therapies to target demyelinating disorders. Among these models, cuprizone (CPZ) intoxication is simple and highly reproducible and renders low mortality levels. The aim of the present study was to use the CPZ model to analyze the mechanisms underlying oligodendrocyte (OLG) viability and differentiation and leading to demyelination. Results show that CPZ-induced demyelination and mature OLG death are mediated by microglial production of pro-inflammatory cytokines, a dysfunction in the mithochondrial respiratory chain and the generation of reactive oxygen species (ROS). Therefore, transgenic animals expressing EGFP under the CNPase promoter exhibit basal hypomyelination and greater susceptibility to CPZ-induced demyelination, as high EGFP expression leads to oxidative stress and mature OLG apoptotic death. As a consequence, partial inhibition of proteasome activity enhances remyelination, reduces microglial recruitment and NF?B activation, thus producing a recovery in the mitochondrial respiratory chain. Finally, our results also show Gal-3 to be secreted by microglia, to induce OLG differentiation and to modulate myelination and the response to demyelination. It may be therefore concluded that OLG viability and differentiation are affected by the production of free radicals and the presence of microglia-secreted factors.